Development of an Innovative Alternative to Hydrogen-Powered Engines for Unmanned Aerial Vehicles - Mamadjanov Lochinbek Yusupovich (Genius Journals, 2022)
New energy sources such as solar energy and hydrogen energy have been applied to the Unmanned Aerial Vehicle (UAV), which could be formed as the hybrid power sources due to the requirement of miniaturization, lightweight, and environmental protection issue for UAV. Unmanned Aerial Vehicle (UAV) hydrogen-powered technology is significantly related to the flight performance of UAVs, which has become one of the most important development directions of aviation. This article presents and discusses the classification, working principles, characteristics, and critical technologies of fuel cells. Additionally, future technologies and development, including the high-power density motors, converters, and power supplies are discussed for hydrogen-powered engines of UAVs
Keywords: UAV; hydrogen powered engine; energy management strategy; engines